Financial Assistance for MSMEs in PRM Blagung in Increasing Resilience and Sustainability Business - Ashar Mukhammad Akbar; Eskasari Putri; Abid Ramadhan; Qodri Royani; Kholid Jundi Ar-Ridho; Erma Setiawati (Abdi Psikonomi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting economic growth and improving community welfare. However, many MSMEs still face challenges in financial management, such as inadequate bookkeeping practices, mixing personal and business finances, and a limited understanding of financial reports. These conditions affect the sustainability and resilience of businesses in facing economic uncertainty and market competition. This community service program aimed to improve the financial management capacity of MSME actors through financial assistance and training activities. The methods used in this program included observation, interviews, socialisation, training, and direct mentoring related to simple financial recording, cash flow management, and preparation of basic financial statements. The activities were carried out through participatory approaches to ensure that participants could understand and apply the materials effectively. The results of the program showed that MSME actors experienced increased understanding and skills in managing business finances, particularly in recording income and expenses, separating personal and business finances, and preparing simple financial reports. In addition, participants became more aware of the importance of financial planning in supporting business sustainability. Therefore, financial assistance activities can contribute positively to strengthening MSME resilience and improving their managerial capabilities in developing sustainable businesses.